2010
DOI: 10.1093/carcin/bgq157
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene induces cell growth inhibition by altering mevalonate pathway and Ras signaling in cancer cell lines

Abstract: Several evidences suggest that cancer cells have abnormal cholesterol biosynthetic pathways and prenylation of small guanosine triphosphatase proteins. Tomato lycopene has been suggested to have beneficial effects against certain types of cancer, including that of prostate, although the exact molecular mechanism(s) is unknown. We tested the hypothesis that lycopene may exert its antitumor effects through changes in mevalonate pathway and in Ras activation. Incubation of the Ras-activated prostatic carcinoma LN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 49 publications
7
99
0
2
Order By: Relevance
“…Androgen is an important biological effector of prostate cancer progression (17). Many studies have demonstrated that phytochemicals can effectively inhibit the apoptosis and proliferation of prostate cancer cells (18)(19)(20)(21)(22). Chun et al reported inhibition of cell viability and apoptosis of Pca cells treated by andrographolide, which is extracted from a medicinal plant (23).…”
Section: Introductionmentioning
confidence: 99%
“…Androgen is an important biological effector of prostate cancer progression (17). Many studies have demonstrated that phytochemicals can effectively inhibit the apoptosis and proliferation of prostate cancer cells (18)(19)(20)(21)(22). Chun et al reported inhibition of cell viability and apoptosis of Pca cells treated by andrographolide, which is extracted from a medicinal plant (23).…”
Section: Introductionmentioning
confidence: 99%
“…10 It is also suggested to inhibit ROS production and decrease the phosphorylation of extracellular signal-regulated kinase (ERK), which results in the inhibition of cancer cell growth. 34,48,49 Lycopene inhibited phosphorylation of ERK, which is a major regulator of cell proliferation, apoptosis, and differentiation in gastric cells, as well as hepatocarcinoma cells.…”
Section: Cancermentioning
confidence: 99%
“…28 A prospective study of tomato products (lycopene) was associated with decreased prostate cancer risk. 30 …”
Section: Lycopenementioning
confidence: 99%